Agency, Patronage and Power in Early Modern English Translation and Print Cultures: The Case of Thomas Hawkins - Guénette, Marie-France (TTR, 2016)
At the English court of Queen consort Henrietta Maria (1625-1642), translation was used as a political tool, partly to impose the queen’s linguistic, cultural and Catholic heritage on Calvinist England. The queen played a pivotal role as a patron of the arts and an agent of Anglo-French cultural relations, and many translators dedicated texts to her in the hopes of winning her favour. This article focuses on “translating agents” (Buzelin, 2005), i.e. translators, printers and patrons, operating in the political, religious and literary networks in and around the Queen’s court. My research draws on scholarship on the cultural and ideological aspects of translation in Stuart Court culture and builds on recent studies on the intersection between translation and print in early modern Europe. I study patterns of patronage, literary production, and text circulation; and I probe the political, social, religious, and print networks involved in the production of translations associated with the Queen’s court, and extending well beyond its social or geographical boundaries. I examine translations using digital catalogues (Early English Books Online, Renaissance Cultural Crossroads, Cultural Crosscurrents in Stuart and Commonwealth Britain), and conduct paratextual analyses of translations dedicated to Henrietta Maria. In this article, I study translator Thomas Hawkins by using data from Six Degrees of Francis Bacon and the Oxford Dictionary of National Biography. Hawkins was a key translating agent who operated in transnational Catholic print networks and whose translations of Jesuit Nicolas Caussin’s La Cour Sainte found their way into social and literary networks around the Queen’s court. I situate Hawkins in the political and ideological contexts of the time and show how he promoted Catholic devotional literature in his capacity as agent of translation, culture and ideology. Hawkins’s case illustrates how agency, patronage and power come together in early modern England’s culture of printed translations.